2017
DOI: 10.1073/pnas.1706643114
|View full text |Cite
|
Sign up to set email alerts
|

MitoNEET-dependent formation of intermitochondrial junctions

Abstract: MitoNEET (mNEET) is a dimeric mitochondrial outer membrane protein implicated in many facets of human pathophysiology, notably diabetes and cancer, but its molecular function remains poorly characterized. In this study, we generated and analyzed mNEET KO cells and found that in these cells the mitochondrial network was disturbed. Analysis of 3D-EM reconstructions and of thin sections revealed that genetic inactivation of mNEET did not affect the size of mitochondria but that the frequency of intermitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 26 publications
4
50
0
Order By: Relevance
“…This study also provided evidence that MFNs are not required for IMJ formation and that IMJs are dynamic structures, the amount and function of which are dynamically regulated by the bioenergetic state of the mitochondrion. It was recently demonstrated that knockdown of MitoNEET (CDGSH iron-sulfur domain-containing protein 1 or CISD1), a dimeric outer membrane protein, reduced IMJ frequency (402). This suggests that MitoNEET plays a role in the regulation of IMJ formation.…”
Section: Role Of Mitoneetmentioning
confidence: 99%
“…This study also provided evidence that MFNs are not required for IMJ formation and that IMJs are dynamic structures, the amount and function of which are dynamically regulated by the bioenergetic state of the mitochondrion. It was recently demonstrated that knockdown of MitoNEET (CDGSH iron-sulfur domain-containing protein 1 or CISD1), a dimeric outer membrane protein, reduced IMJ frequency (402). This suggests that MitoNEET plays a role in the regulation of IMJ formation.…”
Section: Role Of Mitoneetmentioning
confidence: 99%
“…Lastly, antimycin A (15μM) and rotenone (15μM), inhibitors of complex III and I, were added to shut down ETC function, revealing the non-mitochondrial respiration. Mitochondrial reserve capacity (spare capacity) was calculated by subtracting basal respiration from maximal respiratory capacity[38].3.8. Analysis of cardiolipin content3T3-L1 cells were seeded in cover slips placed in the culture plate and differentiated to adipocytes.…”
mentioning
confidence: 99%
“…Cardiac mitochondria isolated from mitoNEET‐deficient mice demonstrate a reduced oxidative capacity (Wiley et al ., ). Loss of mitoNEET in mouse embryonic fibroblasts (MEFs) reduces mitochondrial respiration, although this bioenergetics change appeared to be due to lower numbers of mitochondria (Vernay et al , ). We found reduced mitochondrial membrane potential in NIH/3T3 fibroblast cells following mitoNEET overexpression, which correlated with lower ATP levels, consistent with previous findings in fibroblasts (Kusminski et al , ).…”
Section: Discussionmentioning
confidence: 99%